Development of two-dimensional ensembles of plasmonic nanostructures for surface enhanced raman scattering (SERS) - Duan, Bo (2015)
In this thesis, I developed new strategies towards two-dimensional (2D) ensembles of plasmonic nanostructures and explored their uses as Surface Enhanced Raman Scattering (SERS) substrates. The intense electromagnetic field surrounding plasmonic metallic nanostructures, resulting from the excitation of localized surface plasmon resonance (LSPR), plays a major role in the enormous amplification of the Raman signal for molecules in their close proximity. Major challenges exist in the development of SERS substrate with a high density of hotspots and a built-in mechanism for selected analytes, which are is of considerable interest for achieving improved fundamental understanding on the structure-SERS activity correlation and practical sensing applications. To address these challenges, I took advantages of recent advances in wet-chemical synthesis and interfacial assembly of inorganic nanostructures to develop 2D arrays of plasmonic nanostructures with tailored spectroscopic profiles for optimized SERS signal amplification. Their high SERS activity, coupled with the built-in mechanisms for selective enrichment of analyte molecules at SERS hotspots, offered the possibility to detect a broad range of targets, from small chemical molecules to large biomolecules such as nucleic acids that of considerable current interest for water quality management, food safety screening, and medical diagnostics.